The influence of ball possession on the result of the first division games of the São Paulo 2019 championship - Silva Junior, Osvaldo Tadeu da (2021)
Introduction: Among the variables that help in the good performance of a team, ball possession has been an important factor, given that many research relate ball possession to successful matches. Objective: the present study aimed to evaluate the influence of ball possession on the results of the games of the São Paulo first division championship in the year 2019. Materials and Methods: A descriptive research with a correlational approach was carried out using observation, recording and data analysis. 64 official games of the first division of the São Paulo championship in 2019 were analyzed. The data were observed directly through video analysis and the analysis and recording of the statistical data of the match carried out in real time through the DartFish EasyTag mobile application. Results: The results obtained showed a significant difference between win and defeat (52.0 ± 0.9 and 45.0 ± 0.8; p = 0.03) and correlation between the total time of possession in minutes with the number of wins (r2 = 0.55, p≤0.05). Conclusion: The study showed that there was a significant positive influence of ball possession on the results of matches in the São Paulo championship in series A1 in 2019.